(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
In the contemporary era of globalisation, the cultivation of mutual understanding between diverse cultures and civilisations, in addition to the countering of the vices of extremism and fanaticism, has become increasingly paramount. The scientific and spiritual legacy of Uzbekistan’s great ancestors – Imam al-Bukhari, Imam al-Tirmidhi, and Imam al-Maturidi – serves, in such complex circumstances, as a universal programme of humanism and tolerance. The present article is dedicated to the analysis of the essence of these scholars’ heritage, the goal behind its presentation at the United Nations (UN) and its role as a solution to contemporary global problems.